East Asia in crisis from being a miracle to needing one? - Garnaut, Ross; McLeod, Ross H. (London Routledge, 1998)
The current economic crisis in East Asia is unprecedented in world economic history. This book collates the thoughts of leading experts on the Asian economy and offers a broad and thorough analysis of the situation.
The East Asian crisis / Ross Garnaut -- Indonesia / Ross H. McLeod -- Thailand / Peter G. Warr -- Korea / Heather Smith -- Malaysia / Prema-chandra Athukorala -- China / Ligang Song -- Vietnam / Suiwah Leung and Le Dang Doanh -- India / Sisira Jayasuriya -- The Philippines / Ponciano Intal Jr. [and others] -- Singapore and Hong Kong / Yuk-shing Cheng [and others] -- Taiwan / Shirley W.Y. Kuo and Christina Y. Liu -- Japan / Akiyoshi Horiuchi -- Australia / David Gruen, Brian Gray and Glenn Stevens -- Internationally mobile capital and the global economy / Warwick J. McKibbin -- The role of the International Monetary Fund / David C.L. Nellor -- Will Mexico's recovery from crisis be a model for East Asia? / David D. Hale -- The role of prudential regulation / George Fane -- Exchange rate regimes for the future / Alan A. Walters -- Long-term implications for developing countries / Hadi Soesastro -- The new era of financial fragility / Ross H. McLeod -- Economic lessons / Ross Garnaut.
Includes bibliographical references (pages [367]-380) and index.
Keywords: International trade; Asia -- Commercial policy; Asia -- Economic policy; Asia -- Foreign economic relations; Asia -- Economic conditions -- 1945- .